A CHECKLIST OF TETTIGONIIDAE (ORTHOPTERA : TETTIGONOIDEA) FROMUTTAR PRADESH STATE, INDIA - FAROOQI, MOHD KALEEMULLAH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2016)
A survey of Tettigoniid fauna of Uttar Pradesh State, India was carried out during the period 2013 to 2015. The collected material includes thirteen species belonging to ten genera and four subfamilies. Twelve species, nine genera and two subfamilies are reported for the first time from this region.